Addressing non-communicable diseases in the Western Cape, South Africa - Nasheetah Solomons; H. Salome Kruger; Thandi R. Pouane (SAGE Publishing, 2019)
Background: Chronic non-communicable diseases (CNCDs) are increasing with grave consequences to countries' development. The purpose of this study was three-fold: (1) to determine challenges PURE study participants faced regarding CNCD interventions and what they required from a CNCD intervention programme, and (2) to explore courses of action Department of Health (DoH) officials thought would perform best, as well as (3) to determine what DoH officials perceive to be obstacles in addressing the CNCD epidemic. Design and methods: A subsample of 300 participants from the Prospective Urban and Rural Epidemiological study's Western Cape urban cohort and six key officers from the DoH were recruited to participate in this cross-sectional study. Questionnaires were used in face-to-face interviews with the PURE study participants and DoH officials, together with the multi-criteria mapper (MCM) interviewing method with the latter. Results: Most PURE participants were overweight/obese, but not keen to participate in weight loss interventions. They sought education on foods associated with weight gain, shopping lists, cooking lessons and recipes from CNCD intervention programmes. Department of Health officials regarded the integration of health services, community participation, amongst others as the most favourable options to address the CNCD epidemic. Conclusions: The integration of health services, community participation, food taxation and improving inter-sectoral partnerships were viewed as the most feasible options to address the CNCD epidemic according to the DoH officials. At community level, the needs for education and practical hints were expressed. Current CNCD interventions should be adapted to include the context-based needs of communities.